Production of purified bioactive coagulant from Moringa Oleifera by microfiltration for low turbidity water treatment - Ali, Eman N. (Kulliyyah of Engineering, International Islamic University Malaysia, 2010)
This study is focused on developing an efficient processing technique for Moringa oleifera seeds to produce natural coagulant for use in drinking water treatment. The produced natural coagulant can be used as an alternative to aluminum sulphate and other coagulants worldwide for water treatment. The use of present coagulant materials produce high sludge volumes needs pH adjustments, which means adding more chemicals, and the cost of water treatment is increasing rapidly. A potential solution to these problems is the production of a new natural, renewable, environmentally friendly and safe coagulant/flocculants from Moringa oleifera seed to be used in drinking water treatment. This study investigates processing Moringa oleifera seeds to concentrate the bio-active constituents which have coagulation activity. Moringa oleifera seeds were processed for oil extraction using electro thermal soxhlet. Isolation and purification of bio-active constituents was done by chromatography technique. HPLC was used to determine the molecular weight of the bio-active constituents. The molecular weight of bio-active constituents was in a low range of between 1000 – 6500 Dalton. The importance of determining the molecular weight of bio-active constituents is to find the cut off size for the proposed cross flow filtration (ultrafiltration) method. The bio-activity was determined using conventional jar test procedures, using synthetic water and river water samples. The major water quality control parameters monitored during the study was the residual turbidity for the synthetic and river water with low, medium, and high initial turbidity. The results showed residual turbidity of less than 5 NTU which is recommended by World Health Organization (WHO). The turbidity removal was found to be 95.5%, 98.5%, and 99.3% for low, medium, and high turbidity river water samples, respectively. The proposed method to isolate and purify the bio-active constituents is the cross flow filtration method, which produced the natural coagulant with very simple technique (oil extraction; salt extraction; and microfiltration through 0.20 μm). The water treatment parameters of low speed, mixing time, and the dose of processed Moringa oleifera were optimized. The optimum conditions were: 40 rpm (low speed) with mixing time of 41.28 min, the dose of processed Moringa oleifera was 0.69 mg/L. The optimum conditions of regression model were verified using synthetic and river water with low turbidity. The regression model was highly significant with p-value < 0.01 for all model terms. The turbidity removal was up to 95.1% using low initial turbidity river water without any additives. The initial river water turbidity of 32.4 NTU was reduced to residual turbidity of 1.6 NTU by using 0.75 mg/L of processed Moringa oleifera with low mixing speed of 40 rpm for 41 minutes. The microfiltration method is considered to be a practical method which needs no chemicals added. The natural coagulant produced was used with low dosages to get high turbidity removal which considered to be a breakthrough in this study and recommended to be scaled up for industry level. This product is commercially valuable at the same time it is minimizing the cost of water treatment. The production of this alternative coagulant locally can contribute to the economic development of Malaysia. The by-products (cooking oil, activated carbon, animals feed, and fertilizer) can be of an additional advantage. It is concluded that this is a zero waste industry.